Analisis Pengaruh Faktor Internal Rumah Sakit Terhadap Kepatuhan Pengelolaan Klaim Jaminan Kesehatan Nasional Sebagai Rekomendasi Pencegahan Klaim Pending (Studi Di Rsud Dr. Mohammad Zyn Sampang) - Suhendra , Felix Michael (Syntax Literate, 2025)
This study aims to analyze the influence of internal factors within hospitals on the compliance of managing National Health Insurance (JKN) claims at RSUD dr. Mohammad Zyn Sampang. The factors analyzed include organizational and individual factors that affect JKN claims management. This research uses a quantitative approach with a cross-sectional design, involving 104 employees involved in JKN claims management, selected using Proportionate Stratified Random Sampling. The results show that organizational factors such as regulations, education and training, monitoring and evaluation, as well as sanctions and rewards significantly influence compliance in claims management. Additionally, individual factors such as age, length of service, knowledge, discipline, motivation, and accuracy also affect compliance. Based on these findings, this study recommends improving compliance in JKN claims management by enhancing education and training, as well as implementing more effective sanctions and rewards at RSUD dr. Mohammad Zyn Sampang.